CTNI-33. DEBIO1347, AN ORAL FGFR INHIBITOR: RESULTS FROM A SINGLE CENTER STUDY IN PEDIATRIC PATIENTS WITH RECURRENT/REFRACTORY FGFR ALTERED GLIOMAS. (9th November 2020) - Farouk Sait, Sameer; Rosenblum, Marc; Bale, Tejus; Haque, Sofia; Gilheeney, Stephen; Spatz, Krisoula; Prince, Daniel; Ibanez, Katarzyna; Dunkel, Ira; Karajannis, Matthias
Abstract: BACKGROUND: Oncogenic driver alterations in fibroblast growth factor receptors (FGFRs) are present in a subset of pediatric gliomas. Debio1347 is an orally available, highly selective FGFR 1–3 inhibitor with a favorable safety profile and encouraging preliminary clinical activity in an adult phase 1 study. METHODS: We treated five children with progressive/refractory CNS tumors harboring an FGFR gene alteration with Debio1347 on single patient use protocols. Patients were treated using the 20 mg tablet formulation at the adult recommended phase 2 dose (80 mg/1.73 m 2 ′ BSA once daily). RESULTS: All adverse events (AEs) were grade 1–2. Most common treatment-related AEs were hyperphosphatemia, ALT elevation and hypoalbuminemia. Two patients met criteria for partial response and two patients had stable disease. A 13-month-old patient with a spinal cord high-grade glioma harboring two FGFR1 mutations had tumor reduction of 96.3% maintained for 11 months. A 26 month-old patient with a pilomyxoid astrocytoma harboring an FGFR1-TACC1 fusion had a tumor reduction of 74.5% maintained for 9 months. Prolonged disease stabilization and clinically significant improvement in visual function was noted in an eight year-old patient with metastatic suprasellar pilomyxoid astrocytoma harboring two FGFR1 mutations (14 months overall and sustained for 6 months off therapy) and in a 14 year-old patient with posterior fossa glioneuronal tumor harboring an FGFR3-TACC3 fusion (26 months and ongoing). CONCLUSIONS: FGFR targeted therapy with Debio1347 demonstrated tolerable toxicity and promising anti-tumor efficacy in pediatric patients with recurrent/refractory FGFR altered gliomas. Further studies in this population are warranted.